Toward a Truly Beneficial AI Companion: A Call for Dialogue with Authors and Readers of the Journal of NeuroPhilosophy - Ludvig, Nandor (Journal of NeuroPhilosophy, 2025)
This Open Letter outlines a reasonable plan to create at least one truly beneficial AI companion for humankind: a semiconductor-based entity programmed to possess its own Soul. This Soul would represent a synthesis of the identities, consciences, wills, and missions of sages and other exemplary figures throughout human history. The author invites those interested in this vision of AI development to share their perspectives—whether in support of or in opposition to the proposed plan.